Public Perception of Personal Data Privacy in the Digital Era - Afhdal, Afdhal; MS, Syaifullah (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
Public perception of personal data privacy in the digital era shows that there is a growing awareness of the importance of protecting personal information. People are beginning to understand that personal data is a valuable asset that is vulnerable to misuse in various forms, such as fraud, identity theft, and commercial abuse. However, this awareness has not been fully accompanied by concrete actions in maintaining data security, because there are still many individuals who neglect the use of social media, applications, and other digital services. In addition, some people view that personal data protection is not only an individual responsibility, but also requires strong regulations from the government and a commitment to transparency from digital service providers. This emphasizes that efforts to maintain personal data privacy must be carried out collaboratively between individuals, the community, the government, and the private sector. Thus, it can be concluded that although the public has an awareness of the importance of personal data privacy, the biggest challenge lies in the consistency of safe digital behavior and the strengthening of regulations that are able to provide comprehensive protection in an increasingly complex digital era